Gender - specific differences in perception of menu labelling, witnessed among Hospitality Management students - Krešić, Greta; Pleadin, Jelka; Liović, Nikolina; Kučan, Petra; Vujačić, Vesna; Šušnić, Saša (2018)
Since nutrition labelling is obligatory for all packed food circulating across the European Union (EU), out-eating people demand, ever more often, to be provided with proper nutrition information on food they are eating through the restaurant menu. Given that, at present, no EU laws and regulations mandate nutritional menu labelling, this study aimed to explore a possible relationship between the perception of the need for menu and packed food labelling in a group of Hospitality Management students (n=324; out of which 84 men and 240 women). To that end, a comprehensive three-section questionnaire comprising demographic data, the perception of the need for menu labelling and questions about packed food labelling was developed. The perception of the need for menu labelling was assessed using a five-point Likert scale, the answers thereby scoring from 1 (strongly disagree) to 5 (fully agree). The students of both genders consider menu-delivered nutritional information important (3.59±0.95) for making healthier food choices (3.96±0.98) and achieving better caloric intake control (3.81±1.07). Health impact of menu labelling is more appreciated by female as compared to male students. Students did not perceive menu labelling as a significant cost for the restaurant management (2.67±1.17). The results confirmed that in students of both genders there exists a significant correlation between their habit of reading nutrition labels and a positive perception of menu labelling (p=0.001), the perception of menu labelling health impact (p<0.001) and the perception of menu labelling as a means to an end of better energy intake control (p<0.001). However, when it comes to energy value labelling, a significant correlation was seen solely among female students. The results of multiple regression analysis confirmed that, unlike male students, female students perceive food labelling as a strong predictor of menu labelling intention (nutrition label reading habit, β=0.17
Bibliografija: str. 10-11.
Abstract.
Keywords: Hrana -- Prehrambeni proizvodi -- Deklaracija proizvoda -- Nutritivna deklaracija -- Ugostiteljstvo -- Studenti